Anglicism in Indonesian - Azizah, Nurul (Universitas Cokroaminoto Palopo, 2018)
This article discusses a language phenomenon currently occurring in Indonesia, which is related to borrowing English words with the addition of a prefix ng-/nge in the Indonesian. The purpose of this article is to show how some English words are borrowed in Indonesian and what changes occur within this borrowing process which will be seen on two linguistic levels (phonological and semantic). The data were collected through an observation either in writing forms found in social media as well as oral form used in daily conversations. The interim results show that phonologically, in general the loan words follow the Indonesian phonological rules with little divergence in certain cases. From the semantic analysis it was found that these Anglicism words can be divided into three categories based on their meanings: restriction, expansion and static.